EKSKLESIOLOGI PENTAKOSTA DALAM BAYANG‑BAYANG TEKNOLOGI: GEREJA DAN KOMUNITAS DALAM ZAMAN HYPERCONNECTED MENUJU GEREJA YANG KONTEKSTUAL DI ERA SOCIETY 5.0 - Stefany Yosephine Edrika; David Jullen Kather; Elizama Gulo (CV. Denasya Smart Publisher, 2025)
This study explores the relevance of Pentecostal ecclesiology in the digital era of Society 5.0, emphasizing the need for theological reflection on how technology reshapes church life, worship, and spiritual experience. The main objective is to analyze how Pentecostal theology, rooted in the experience of the Holy Spirit, can respond to the challenges of a hyperconnected society without losing its doctrinal integrity. Using a qualitative method with a theological literature review, this research synthesizes various sources discussing Pentecostal theology, digital ecclesiology, and the intersection between faith and technology. The findings reveal that Pentecostal ecclesiology must reinterpret its understanding of the church as a Spirit-driven community that transcends physical and digital boundaries. The study identifies opportunities for hybrid worship models, digital discipleship, and online spiritual communities, alongside challenges related to authenticity, sacramentality, and ethical digital engagement. Furthermore, it highlights the importance of Spirit-led discernment, digital literacy, and leadership transformation to sustain the church’s spiritual vitality amid technological disruption. The implication for further research is the development of contextual Pentecostal ecclesiology that integrates theological depth with technological adaptability, ensuring that digital innovation enhances rather than diminishes the communal and incarnational essence of the church